English for international tourism: Pre - intermesiate workbook - Dubicka, Iwonna (Pearson Education Limited, 2003)
This is a fantastic workbook with excellent, practical exercises. It specifically targets not only the vocabulary needed for international tourism, but also offers practice with reading and writing emails, understanding hotel websites, booking appropriate tours, airline regulations, safety & security, health services and much, much more.